2003
DOI: 10.1046/j.1523-1747.2003.12495.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal COX-2 Induction Following Ultraviolet Irradiation: Suggested Mechanism for the Role of COX-2 Inhibition in Photoprotection

Abstract: The cyclooxygenase isoforms, COX-1 and COX-2, are involved in the biosynthesis of prostaglandin E2, a major prostaglandin involved in epidermal homeostasis and repair. Cancer originating in the epidermis can develop when keratinocyte proliferation and apoptosis become dysregulated, resulting in sustained epidermal hyperplasia. COX-2 inhibitors, which demonstrate significant in vivo selectivity relative to COX-1, suppress both ultraviolet-induced epidermal tumor development and progression, suggesting that pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 41 publications
(63 reference statements)
8
118
0
5
Order By: Relevance
“…The role of Erbb2 in promoting cell survival may also occur through increased antiapoptotic gene expression, such as Ghr 57 and Ptgs2, which has been shown to promote survival by decreasing apoptosis after UV exposure to keratinocytes. 58 Consistent with these data, cell culture experiments to validate the microarray analysis demonstrated that inhibition or knockdown of Erbb2 increased apoptosis slightly but significantly after UV, implying Erbb2 enhances cell survival after UV. However, the biological significance of an effect of this magnitude remains unclear.…”
Section: Discussionsupporting
confidence: 63%
“…The role of Erbb2 in promoting cell survival may also occur through increased antiapoptotic gene expression, such as Ghr 57 and Ptgs2, which has been shown to promote survival by decreasing apoptosis after UV exposure to keratinocytes. 58 Consistent with these data, cell culture experiments to validate the microarray analysis demonstrated that inhibition or knockdown of Erbb2 increased apoptosis slightly but significantly after UV, implying Erbb2 enhances cell survival after UV. However, the biological significance of an effect of this magnitude remains unclear.…”
Section: Discussionsupporting
confidence: 63%
“…The effects of prostaglandins and the cross talk between prostaglandin receptors and their signaling intermediates are of intense interest because of the diverse effects of prostaglandins on cell growth, differentiation and carcinogenesis [3,38,[41][42][43]. While the effects of PGE 2 on epidermal keratinocytes are reasonably well understood [1,[43][44][45], there has been much less investigation in the effects of PGE 2 on human melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Both EPA and AA are susceptible to enzymatic and nonenzymatic peroxidation of membrane lipids, thus generating large quantities of reactive cytotoxic products that then could control cell proliferation. 39 Elevated COX-2 expression has been reported in pancreatic cancer, 40,41 esophageal cancer, 42 gastric cancer (in which its expression may be a predictor of survival), 43 skin cancers (including melanoma), [44][45][46][47] prostate cancer, [48][49][50][51][52][53][54][55] bladder cancer, [56][57][58] lung cancer (in which expression may also correlate with prognosis), 59,60 ovarian cancer (which also correlates with poor prognosis), 61 cervical cancer (COX-1 is expressed as well), 62 and B-cell lymphoma. 63 Expression in breast cancer has been reported in 36% to 79%.…”
Section: Dommels Et Almentioning
confidence: 99%